2016
DOI: 10.1177/1708538115604089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of illness severity scoring systems and risk prediction in vascular intensive care admissions

Abstract: The good discrimination of these scoring systems indicates their value as an adjunct to clinical assessment but should not be used on an individual basis as a clinical decision-making tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…Other studies have shown that these complications are associated with an increase in operative deaths and other short-term measures of death, but most have treated these complications in isolation and even fewer have studied long-term outcomes. Similar to other studies, we found that cardiac arrest, need for reoperation in the postoperative period, new need for dialysis, and multisystem organ dysfunction were associated with increased death [19][20][21][22][23][24][25][26]. However, our study expands on this knowledge by showing the relative contributions of different complications to years of life lost and adjusts for the fact that patients can have multiple complications but only one death.…”
Section: Commentsupporting
confidence: 86%
“…Other studies have shown that these complications are associated with an increase in operative deaths and other short-term measures of death, but most have treated these complications in isolation and even fewer have studied long-term outcomes. Similar to other studies, we found that cardiac arrest, need for reoperation in the postoperative period, new need for dialysis, and multisystem organ dysfunction were associated with increased death [19][20][21][22][23][24][25][26]. However, our study expands on this knowledge by showing the relative contributions of different complications to years of life lost and adjusts for the fact that patients can have multiple complications but only one death.…”
Section: Commentsupporting
confidence: 86%
“…There are many scoring systems such as Acute Physiology and Chronic Health Evaluation (APACHE) II, III and IV, Simplified Acute Physiology Score (SAPS), Mortality Prediction Model (MPM), Multiple Organ Dysfunction Score (MODS), Sepsis-related Organ Failure Assessment Score (SOFA), Logistic Organ Dysfunction Score (LODS), and so on. [4,5] APACHE II includes an acute physiology score, age points, and chronic health points. [6] Within the first 24 hours of patient admittance, the worst value for each physiological variable is calculated into an integer score ranging from 0 to 71.…”
Section: Introductionmentioning
confidence: 99%